2023
DOI: 10.1149/2162-8777/acda60
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Copper Thin Films on Screen Printed Carbon Electrodes towards Electrochemical Sensing of Nitrate

Abstract: Accurate and frequent monitoring of NO3− levels in water bodies is crucial for human health and environment. Here, copper (Cu) thin films electrodeposited on screen-printed carbon electrodes (SPCEs) were explored as an electrochemical sensing platform for the detection of NO3− in water. Scanning electron microscopy with energy-dispersive X-Ray analysis, X-Ray diffraction analysis, and X-ray photoelectron spectroscopy was employed to characterize the morphology and composition of the thin film modified electrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Nitrate is usually detected using pulse voltammetry (DPV) and linear scanning voltammetry (LSV) methods. , In electroanalytical chemistry, square wave voltammetry (SWV) and differential pulse voltammetry (DPV) are often observed to be more sensitive techniques than linear scanning voltammetry (LSV) due to their sampling methods that minimize the charging current (non-Faraday process). However, some research studies have shown that LSV is more sensitive than DPV in electrochemical testing .…”
Section: Resultsmentioning
confidence: 99%
“…Nitrate is usually detected using pulse voltammetry (DPV) and linear scanning voltammetry (LSV) methods. , In electroanalytical chemistry, square wave voltammetry (SWV) and differential pulse voltammetry (DPV) are often observed to be more sensitive techniques than linear scanning voltammetry (LSV) due to their sampling methods that minimize the charging current (non-Faraday process). However, some research studies have shown that LSV is more sensitive than DPV in electrochemical testing .…”
Section: Resultsmentioning
confidence: 99%